The Effect of Scientific Literacy Approach with Discovery Learning Model toward Physics Concepts Understanding - Saputra, I Gede Purwana Edi; Sukariasih, Luh; Nursalam, La Ode; Desa, Susilo Sudarman (Universitas Muhammadiyah Makassar, 2022)
Scientific literacy is essential in our modern society today due to many problems related to science and technology. This study aims to determine the effect of the scientific literacy approach using the discovery learning model on students' understanding of physics concepts. The method of this research is a true experimental research using post-tests only control group design. This research was conducted at SMA Negeri 1 Watubangga. The sample of this study consisted of two classes, namely the experimental class, which was taught with scientific literacy approach using the discovery learning model, and the control class which was taught by using the direct learning model. Sampling was carried out using a random sampling technique so that class X1 was chosen as the experimental class and X2 as the control class. The data analysis technique used was descriptive and inferential analysis. The results showed that students' understanding of physics concepts in the experimental class is in a good category while in the control class is in the medium category. The inferential test shows t-count > t-table (6.85 > 1.98). This means that there is a significant difference in understanding of physics concept between the experimental and control group. This study concludes that the use of a scientific literacy approach with a discovery learning model has an effect on students' understanding of physics concepts.